2016
DOI: 10.1016/j.kjms.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on biochemical recurrence after radical prostatectomy

Abstract: The aim of the study was to evaluate the relationship between patient's age and biochemical recurrence (BCR) after radical retropubic prostatectomy (RRP). Data from RRP applied to 305 patients with clinically localized prostate cancer were included in the study. Patients were divided into the three age groups, < 60 years, 60-70 years, and > 70 years. The groups were compared regarding adverse pathological findings on RRP specimen, BCR, and biochemical recurrence-free survival (bRFS) rates. The rates of positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Stephenson et al (22) validated two groups of patients and had summarized similar postoperative C-index value (0.81 vs. 0.79). Ozden et al (23) recruited 305 patients and concluded that age was not a significant factor to predict BRC, which was similar to our study. Freedland et al (24) found that the percentage of biopsy cores involvement by cancer was a better predictor than the number of cores involved by cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Stephenson et al (22) validated two groups of patients and had summarized similar postoperative C-index value (0.81 vs. 0.79). Ozden et al (23) recruited 305 patients and concluded that age was not a significant factor to predict BRC, which was similar to our study. Freedland et al (24) found that the percentage of biopsy cores involvement by cancer was a better predictor than the number of cores involved by cancer.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of 305 patients investigating the effect of patient age on BCR after RP, no significant relationship was found between age and recurrence (24). Besides, Kunz et al evaluated the tumor characteristics of patients over the age of 70, which showed that patients in this age group had more biologically aggressive tumors than younger patients, but age alone was not an independent marker of survival after RP (25).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In a study of 305 patients investigating the effect of patient age on BCR after RP, no significant relationship was found between age and recurrence. 24 Besides, Kunz et al evaluated the tumour characteristics of patients over the age of 70, which showed that patients in this age group had more biologically aggressive tumours than younger patients, but age alone was not an independent marker of survival after RP. 25 Also in our study, no significant relationship was found between age and BCR, and RFS (P = .974).…”
Section: Discussionmentioning
confidence: 99%